PELATIHAN TEKNIK MUDAH PEMBUATAN DESAIN LOGO DENGAN MENGGUNAKAN CORELDRAW PADA SMK TARBIYAH HAMPARAN PERAK - Muhammad Sabri; Titin Setiawati (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
The development of science and technology continues to grow very rapidly, meanwhile applications in the field of information technology have a major impact in various areas of life, one of which is in the creative industries such as advertising, billboards, graphic design, fashion and digital image processing. At this time graphic design skills are needed in various fields, to support business and organizational needs. On this occasion, we presenters from Universitas Potensi Utama use the CorelDraw application facility to create a Logo. The software used in this training is vector-based. So that the final results obtained are of better quality when enlarged / zoomed. So that the output target of this activity is that participants can implement graphic design both within the school environment in the form of making wall magazines or other announcements and can be implemented in the world of work related to graphic design. This activity aims to improve the knowledge and skills of students in improving the quality of their ability to create attractive graphic designs so that participants can compete to meet the demand for job opportunities and also towards entrepreneurship. The materials given to participants include creating and completing logo designs for business or organizational needs.